The Development of Higher Education Research in Europe
VI, 137 p.
Keywords: Though the book is a contribution to celebrate the 25th anniversary of the Consortium of Higher Education Researchers (CHER), it is not just about the history of the organisation as such. The contributions provide an account of the emergence of higher education as a field of study and research in Europe, its institutionalisation, and its relationships to higher education policy and practice. Furthermore, higher education research in Europe is contrasted to and contextualised by the example of higher education research and scholarship in Australia. The book is useful as an account about the emergence and development of higher education research as a field of study and research in Europe. It will be an interesting and insightful read for all scholars and young researchers wanting to know about higher education research but also for scholars in fields like history of science, disciplinary differentiation, institutionalisation of fields of knowledge and research.